ДО ПИТАННЯ ОРГАНІЗАЦІЙНОЇ СТРУКТУРИ УПРАВЛІННЯ ІННОВАЦІЙНО-ПЕДАГОГІЧНОЮ ДІЯЛЬНІСТЮ У ВНЗ - Шарата, Наталія (Збірник наукових праць Уманського державного педагогічного університету, 2020)
Автором розкрито основні складові структури управління інноваційно-педагогічною діяльністю у вищих навчальних закладах. Виокремлено основні види організаційної структури управління у ВНЗ, що побудовані за класичним принципом, з-поміж яких: лінійна й функціональна організаційна структура управління. Доведено, що перспективними є організаційні структури управління, побудовані за дивізійним і матричним типами, оскільки тільки вони здатні адекватно й оперативно реагувати на зміни як у внутрішньому, так і у зовнішньому середовищі ВНЗ. Автором раскрыты основные составляющие структуры управления инновационно-педагогической деятельностью в высших учебных заведениях. Выделены основные виды организационной структуры управления в вузах, построены по классическому принципу, среди которых: линейная и функциональная организационная структура управления. Доказано, что перспективными являются организационные структуры управления, построенные по дивизионным и матричным типами, поскольку только они способны адекватно и оперативно реагировать на изменения как во внутренней, так и во внешней среде вуза. In the article the writer covers the main components of the governance structure of management innovation and teaching activities in higher education. It is proved that promising are institutional management structure, built on the divisional and matrix types, because they are able to adequately and promptly respond to changes in the internal and external environment of the university. The majority of foreign authors consider the innovation activity to be one of the most important aspects of modern school’s work on the way of development which is characterized by succession and stages. Innovation activity is one of the priority trends of the state economic policy. The main bearers of innovation ability of the nation are higher educational establishments which are fulfilling the tasks of innovation activity intensification. The analysis of innovations development in education mentioned above makes it possible to come to conclusions which are important both for development of innovation component in the activity of modern higher education establishment and formation of system of efficient innovation activity. The innovation activity of higher educational establishments makes it possible to provide a civilized commercialization of knowledge and technologies.